What explains fertility? : evidence from Italian pension reforms - Francesco C. Billari; Vincenzo Galasso (Center for Economic Studies and ifo Institute (CESifo), 2009)
Why do people have kids in developed societies? We propose an empirical test of two alternative theories - children as consumption vs. investment good. We use as a natural experiment the Italian pension reforms of the 90s that introduced a clear discontinuity in the treatment across workers. This policy experiment is particularly well suited, since the consumption motive predicts lower future pensions to reduce fertility, while the old-age security to increase it. Our empirical analysis identifies a clear and robust positive effect of less generous future pensions on post-reform fertility. These findings are consistent with old-age security even for contemporary fertility.
Keywords: H55; J13; D64; 330; old-age security; public pension systems; fertility; altruism; Fruchtbarkeit; Kinder; Investition; Konsumgut; Rentenreform; Bevölkerungsentwicklung; Italien